2009
DOI: 10.1163/156853909x423104
|View full text |Cite
|
Sign up to set email alerts
|

Strategies of song adaptation to urban noise in the house finch: syllable pitch plasticity or differential syllable use?

Abstract: The influence of ambient noise in shaping birdsong attributes has received much attention lately. Recent work shows that some birds sing higher-pitched songs in noisy areas, which may allow them to avoid acoustic interference; yet it is not clear how this is achieved. Higherpitched songs may be produced either by using the same syllable types in quiet and noisy areas, but singing them at a higher frequency in the latter (syllable pitch plasticity), or by using different syllable types in silent and in noisy ci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
57
2
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 104 publications
(64 citation statements)
references
References 33 publications
(48 reference statements)
3
57
2
2
Order By: Relevance
“…Additionally, birds can increase the redundancy of signals so that the message has an increased chance of getting across in noisy environments [6], or sing at times when noise level is lower [7]. Another possibility is to sing higher pitched songs to reduce their acoustic overlap with low-frequency noise [8][9][10][11]. A recent study has shown that urban populations of great tits (Parus major) have an increased minimum frequency in comparison to the countryside populations, and that this modification is best explained as a response to noise perturbation [12].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, birds can increase the redundancy of signals so that the message has an increased chance of getting across in noisy environments [6], or sing at times when noise level is lower [7]. Another possibility is to sing higher pitched songs to reduce their acoustic overlap with low-frequency noise [8][9][10][11]. A recent study has shown that urban populations of great tits (Parus major) have an increased minimum frequency in comparison to the countryside populations, and that this modification is best explained as a response to noise perturbation [12].…”
Section: Introductionmentioning
confidence: 99%
“…Many species improve signal detectability by increasing the minimum frequency of their songs, which, because of the low-frequency nature of anthropogenic noise, can reduce masking effects (e.g. Bermúdez-Cuamatzin et al, 2009;Kirschel et al, 2009;Ripmeester et al, 2010;Verzijden et al, 2010). In our study, the minimum frequency of trills did not differ between treatments, perhaps because the frequency range of red-winged blackbird trills (2.75-5.0kHz) exceeded the frequencies contained in our experimental low-frequency white noise (0-1.83kHz) and exceeded the majority of frequencies produced by traffic (again, traffic noise is concentrated below 3kHz) (Cornillon and Keane, 1977;Halfwerk et al, 2010;Wood and Yezerinac, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Finally, some species increase signal detectability in noisy environments by producing an alternative type of signal with better transmission properties (e.g. Bermúdez-Cuamatzin et al, 2009;Dunlop et al, 2010). Red-winged blackbirds have only a single song type, however, so this strategy is not an option for this species.…”
Section: Discussionmentioning
confidence: 99%
“…The latter result in particular is novel in methodology and conceptual implications, as it strongly suggests the general ability to rapidly respond to fluctuating noise conditions. Although the underlying causal mechanism may vary, such an immediate spectral shift may also explain correlative patterns in other studies on other species (Slabbekoorn and Ripmeester, 2008;Bermudez-Cuamatzin et al, 2009;Parris and Schneider, 2009;Ripmeester et al, 2010). Without experimental data we are currently unable to ascribe those correlative patterns in other species to an evolutionary, ontogenetic or immediate adjustment of singing (Patricelli and Blickley, 2006) (but see Halfwerk and Slabbekoorn, Singing flexibility and highway noise 2009).…”
Section: Potential For Noise Exposure Experimentsmentioning
confidence: 96%